Stabilisasi Tanah Lunak Menggunakan Kombinasi Fosroc Cebex-100 Dan Fly Ash untuk Meningkatkan Nilai CBR - Damayanti, Apta Kania; Kahaditu F, Yerry; Farichah, Himatul (Universitas Nahdlatul Ulama Blitar, 2025)
Soft clay type soil has a low bearing capacity; therefore, a special handling is required by performing soil stabilization. The case study in this research is located in the construction project of Jalan Lingkar Utara (JLU) Lamongan Regency STA 1+000 s/d STA 1+100. The soil stabilization method carried out in this research is using a chemical method that combines fosroc cebex-100 and class C fly ash. 3 variations of the percentage combination of stabilizers used are 20% fly ash + 0.45% fosroc cebex-100 for variation 1, 25% fly ash + 0.45% fosroc cebex-100 for variation 2 and 30% fly ash + 0.45% fosroc cebex-100 for variation 3. The results of this study show that along with the increase in the composition of the combination of stabilizers in the soil can cause an influence on the physical properties of the soil, namely a decrease in the value of water content, specific gravity, Atterberg boundaries, and soil plasticity index. Meanwhile, the mechanical properties of the soil show an increase in the CBR value as the proportion of stabilizers used increases. The original soil CBR value of 5.87% increased to 8.23% in variation 1, to 6.44% in variation 2, and to 6.06% in variation 3.